HUBUNGAN FAKTOR SOSIOLOGIS DAN FAKTOR PSIKOLOGIS TERHADAP PERILAKU MEMILIH MASYARAKAT PADA PEMILIHAN KEPALA DAERAH PELALAWAN TAHUN 2015 DI KECAMATAN BANDAR PETALANGAN (Studi Kasus Desa Lubuk Keranji Timur dan Desa Kuala Semundam) - Chip Chexk Purba; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The process of writing this research is based on a point of view the writer to examine the phenomenon of society in Bandar Petalangan District in the local election of 2015. Through Pelalawan Regency seeing the behavior characterictics one district of two villages with different tendencies and their significant participation in Deciding the selection of the cadidates. This research uses a quantitative correlation a contingency approach to correlate the two approaches in the school of Michigan, the Sociological and Psychological Approach to the behavior of voters in the voting at the location of the object of research. Primary Data were collected through a survey and analysis of documents. Data processing was performed using the program Statistic Package For Social Science (SPSS). Then the data is processed through the Crostabbulation by Chi-square test to see relationships and correlations contingency to see the relationship between the variables studied. The results of this study there was no significant relationship between voting behavior of district community Bandar Petalangan on the elections, Palalawan 2015 based on gender, age, religion, education (Sociological factors) and the factor of the issues that developed, the image of the personality and leadership experience (Psychological factors). While the Researchers found no relationship between behavioral subsequently chose to sociological factors, based on ethnic identity, income level and psychological factors in the identification of party and candidate to the district community programs in local elections Bandar Petalangan Palalawan, 2015.Kata Kunci: Election, Participation, Voting Behaviour,